Unmanned aerial vehicle (UAV)-assisted pesticide application for pest and disease prevention and control in rice - Ragiman, Reddy; Talluri, Kiran Babu; NRG, Varma; B, Vidya Sagar (International Journal of Agricultural and Biological Engineering, 2024)
Unmanned Aerial Vehicles (UAVs) have emerged as innovative tools in agriculture, revolutionizing crop protection practices and the use of pesticide combinations to aid the management of insect pests and diseases in a single application. This research delves into assessing the efficacy of drone-based pesticide spraying utilizing combinations of pesticides to combat insect pests and diseases in rice cultivation. In kharif 2022, the physically compatible combination of insecticides (chlorantraniliprole 18.5% SC and tetraniliprole 200 SC) with fungicides (picoxystrobin 7.5%+tricyclazole 22.5% SC and tebuconazole 50%+trifloxystrobin 25% WG) were administered via drones and compared with conventional Taiwan sprayer. The results indicated that tebuconazole+trifloxystrobin, when applied via drones, exhibited the highest control efficacy against the brown spot, sheath blight, and sheath rot (47.8%, 77.4%, and 75.2% respectively). Moreover, combination treatment i.e., tetraniliprole+(tebuconazole+trifloxystrobin), applied using a drone, achieved the most effective control (78.1%) against grain discoloration. Additionally, drone-based tetraniliprole application showed effectiveness against stem borer and whorl maggot (efficacy rates of 49.1%, 66.6%, and 60.7% for Dead Hearts, White Ear, and Whorl Maggot, respectively). Overall, the pesticide combination treatment i.e., tetraniliprole+(tebuconazole+trifloxystrobin) showed higher control efficacy against all the insect pests and diseases and recorded the highest grain yield of 7995 kg/hm2 with incremental cost benefit ratio (ICBR) of (1:5.63) when sprayed with a drone. Overall, this study underscores the potential of drone-assisted pesticide application in effectively managing multiple insect pests and diseases in rice offering superior precision, efficacy, efficiency, and yield. Keywords: bio-efficacy, drone spraying, drone-based pest management, precision agriculture, pesticide combinations DOI: 10.25165/j.ijabe.20241705.8640 Citation: Ragiman S, Talluri K B, NRG V, B Vidya S. Unmanned aerial vehicle (UAV)-assisted pesticide application for pest and disease prevention and control in rice. Int J Agric & Biol Eng, 2024; 17(5): 88-95.